PENGOLAHAN LIMBAH ORGANIK RUMAH TANGGA SEBAGAI PUPUK ORGANIK CAIR DI KABUPATEN PANDEGLANG - Yeyen Maryani; Agus Rochmat; Herayati; Meri Yulvianti (UIN Sunan Kalijaga, 2022)
The waste problem was one of the priorities of the local government. The waste sorting business started from the beginning, but the management and reprocessing of waste was a separate homework from the Environment Agency. The Untirta Community Service Team offered the processing of organik waste into Liquid Organik Fertilizer (POC) through a fermentation process with the used of EM4. The fermentation process for 7-15 days produced POC which has essential nutrients needed by plants. Giving 1:1 POC to plants increased more fruit and increased color brightness in ornamental plants. Socialization and training activities were carried out in 2 farmer groups in Pandeglang Regency. Direct practice of making POCs and the team giving POCs to participants so that they can be applied directly in their respective places. The socialization activities were supported by the village government and support from the Pandeglang Regency Agricultural Extension Center.